Pengaruh Konsentrasi Milk Clotting Enzyme dari Lactobacillus rhamnosus SKG34 Terhadap Kualitas Keju Lunak - Louis Adisurya, Jeremy; Mayun Permana, I Dewa Gde; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This research was conducted to determine the effect of Milk Clotting Enzyme concentration from Lactobacillus rhamnosus SKG34 on the quality of soft cheese and to determine the concentration of Milk Clotting Enzyme that produced the best quality of soft cheese. This research used a Completely Randomized Design (CRD) with single factor of Milk Clotting Enzyme concentration (16%, 18%, 20%, 22% and 24%). Each treatment was repeated 3 times resulting 15 experimental units. The data were analysed by Analysis of Variance (ANOVA) Test and if the treatment had a significant effect on the variable (P<0,05), then followed by Duncan Multiple Range Test (DMRT). The results showed that Milk Clotting Enzyme concentration had a significant effect on water content, protein content, cheese hardness, and yield. The concentration of 24% Milk Clotting Enzyme produced the best quality of soft cheese with water content of 58.01%, yield 9.34%, protein content 2.68%, cheese hardness 2.68 N, taste was slightly liked, flavour was liked, texture was liked and overall acceptance was liked.